Pedagogical and Technological Perspective in Convergence Blended Learning - Turpo Gebera, Osbaldo (2014)
Since its emergence in the educational context, the blended learning insurgentas a modality with its own identity. According to its evolution, runs through presentiality configured contexts and virtuality. In a first stage, stood as a mixed or combined mode, and then advanced to integration, which resulted in the dilutionof its components. The progressive social changes, technological and cultural towards convergence, today brings a new north-mode, given the confluence of pedagogical and technological mediations in the training process. This position places him in a new trend that more than a possibility, actually represents a more explicable on the future of Blended Learning.